First Records of Five Shorebird Species for Flores, Indonesia: Asian Dowitcher Limnodromus semipalmatus, Kentish Plover Charadrius alexandrines, Ruff Philomachus pugnax, Eurasian Curlew Numenius arquata and Broad-billed - Mark Schellekens (KUKILA, 2009)
This paper documents the first island records of five migrant waders on Flores, Nusa Tenggara, based on 21 brief surveys in east-central and south-central Flores. On 8 October 2004, four Asian Dowitchers Limnodromus semipalmatus and a Kentish Plover Charadrius alexandrinus were seen on Pangabatang Island, a small sand islet off Maumere. At Tambak Koliaduk aquaculture ponds (Maumere), two adult Ruff Philomachus pugnax were recorded on 5 December 2004, and a Eurasian Curlew Numenius arquata on 19 December 2005 . Finally, two Broad-billed Sandpipers Limicola falcin ellus were obser-Ved at Ende estuary in south-central Flores on 17 October 2006. Given the relatively low survey effort in the region, it is likely that most of these species are regular visitors in small numbers to Flores and Timor.